Outcomes of a functional rehabilitation protocol in chronic critical disease by COVID-19: A case report (Research, Society and Development, 2023)
The 2019 novel coronavirus (SARS-CoV-2) is the virus that causes COVID-19. It can cause severe illness, with significant increase in morbidity and mortality rates, requiring the need for hospitalization and mechanical ventilation. This study aims to describe a functional rehabilitation protocol applied to a patient with COVID-19 after 21 days of mechanical ventilation (MV). We report a case of a 56-year-old female patient diagnosed with COVID-19 who presented severe hypoxemic respiratory failure, chronic critical disease, intensive care unit acquired weakness, difficult and prolonged weaning, organ dysfunction, and needed tracheotomy. The patient responded satisfactorily to a late functional rehabilitation protocol showing the importance of well-designed and individualized protocols to achieve maximum functional recovery.